2018
DOI: 10.1111/1365-2656.12823
|View full text |Cite
|
Sign up to set email alerts
|

Transient synchrony among populations of five foliage‐feeding Lepidoptera

Abstract: Studies of transient population dynamics have largely focused on temporal changes in dynamical behaviour, such as the transition between periods of stability and instability. This study explores a related dynamic pattern, namely transient synchrony during a 49-year period among populations of five sympatric species of forest insects that share host tree resources. The long time series allows a more comprehensive exploration of transient synchrony patterns than most previous studies. Considerable variation exis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 80 publications
(145 reference statements)
0
18
0
Order By: Relevance
“…Finally, we would like to put our observations in the context of the studies of transient dynamics in ecology, which appears to be very important and quite common (Hastings et al, 2018) including population synchronization phenomena (Klapwijk et al, 2018). From a mathematical perspective, the idea that the ecologically relevant dynamics is not necessarily the dynamics near and on the attracting synchronization manifold in the phase space is somewhat similar to the idea of importance of transients in ecology.…”
Section: Discussionmentioning
confidence: 83%
“…Finally, we would like to put our observations in the context of the studies of transient dynamics in ecology, which appears to be very important and quite common (Hastings et al, 2018) including population synchronization phenomena (Klapwijk et al, 2018). From a mathematical perspective, the idea that the ecologically relevant dynamics is not necessarily the dynamics near and on the attracting synchronization manifold in the phase space is somewhat similar to the idea of importance of transients in ecology.…”
Section: Discussionmentioning
confidence: 83%
“…Beet armyworm and fall armyworm showed strong synchrony at nearly all times and timescales, whereas for hornworm the predominant pattern was asynchrony, with synchrony occurring only episodically at certain timescales. Such a pattern may be consistent with the occurrence of occasional synchronising events on a background of asynchrony (Klapwijk et al ., ). Some species showed synchrony that appeared to change its dominant period over time, such as cabbage looper, for which synchrony shifted from c .…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, there is evidence that the numerical response of shared predators can synchronize prey herbivore populations (Marcström et al, 1988). Finally, Baltensweiler (1991) and Klapwijk et al (2018) suggested that forest folivore populations may be synchronized when one species reaches outbreak levels causing a reduction in either quantity or quality of a shared foliar resource.…”
Section: Discussionmentioning
confidence: 99%
“…One group of consumer species for which interspecific synchrony is known to commonly occur is in foliage-feeding forest insects (Kawatsu, Yamanaka, Patoèka, & Liebhold, 2019;Klapwijk et al, 2018;Miller & Epstein, 1986;Myers, 1998;Raimondo, Liebhold, Strazanac, & Butler, 2004;Raimondo, Turcáni, Patoèka, & Liebhold, 2004). Several explanations have been proposed to explain synchrony among these folivore populations.…”
mentioning
confidence: 99%
See 1 more Smart Citation